Connecting the covenants: Judaism and the search for Christian identity in eighteenth-century England - Ruderman, Daṿid (Jewish culture and contexts, 2007)
Covenants connected and unconnected : David Nieto and his Anglican adversaries, Humphrey Prideaux and Moses Marcus -- Moses Marcus's conversion to Christianity -- The career of Moses Marcus in London : an expert on Judaism and a defender of religious orthodoxy -- Restoring the "true text" of the Old Testament : William Whiston and his critics, Johann Carpzov and Moses Marcus -- Anthony Collins's attack on William Whiston : could the rabbis ultimately rescue Christianity from its own exegetical crisis? -- On the proper education of an English divine : William Wotton and his learned friends